2018
DOI: 10.1016/j.chest.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Centers for Medicare & Medicaid Services Severe Sepsis and Septic Shock Early Management Bundle and Initial Lactate Measurement on the Management of Sepsis

Abstract: Delays in lactate measurement are associated with delayed antibiotics and increased mortality in patients with initial intermediate or elevated lactate levels. Systematic early lactate measurement for all patients with sepsis will lead to a significant increase in lactate draws that may prompt more rapid physician intervention for patients with abnormal initial values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 22 publications
5
35
0
Order By: Relevance
“…Lactate measurement, which is an important component of a sepsis bundle, has increased dramatically since 2003 and is performed on patients without overt shock [10]. Current evidence indicates the necessity of early lactate measurement in patients with initial intermediate or elevated lactate levels [21][22][23]8,24]. This provided the basis for the proposal of the 1-hour bundle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate measurement, which is an important component of a sepsis bundle, has increased dramatically since 2003 and is performed on patients without overt shock [10]. Current evidence indicates the necessity of early lactate measurement in patients with initial intermediate or elevated lactate levels [21][22][23]8,24]. This provided the basis for the proposal of the 1-hour bundle.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate measurement is an important component of the early management of sepsis, and its optimal execution time is the focus of the current study. Current evidence indicates that delays in the detection time of lactate will lead to an increase in poor prognosis, including death [8][9][10][11]. However, whether the delay of lactate measurement will affect the e cacy of initial lactate on mortality has always been neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that hook-wire localization had lower successful operative field targeting rates, lipiodol localization had the highest overall success rates, and microcoil localization had the lowest complication rates. 1 From a surgeon's perspective, there are other concerns when determining the optimal method of localization, in addition to success rates and complication rates. The location of the pulmonary nodule and the workflow are also important issues.…”
Section: Electromagnetic Navigation-guided One-stage Dual Localizatiomentioning
confidence: 99%
“…We agree with Drs Bakker and Hernandez that our work does not prove a causal relationship between delayed lactate measurements and increased mortality in patients with initially elevated lactate measurements, but rather an association. 1 The fact that this association is no longer significant when adjusted for time to antibiotic and intravenous fluid administration suggests that earlier interventions likely mediate this association. Even after adjusting for severity of illness, we found that abnormal lactate values were correlated with more rapid interventions by clinicians.…”
mentioning
confidence: 99%
“…The study concluded that hook-wire localization had lower successful operative field targeting rates, lipiodol localization had the highest overall success rates, and microcoil localization had the lowest complication rates. 1 From a…”
Section: Electromagnetic Navigation-guided One-stage Dual Localizatiomentioning
confidence: 99%